New Journalist Work Patterns and News Media Production in Pandemic - Erwin Kartinawati; Muhammad Alfikri; Solihah Titin Sumanti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
The pandemic has changed the work order and old patterns that have prevailed in the media. This paper highlights the changing work patterns and news media production in Surakarta City-Indonesia regarding the pandemic. The data were collected by interviews and observations of journalists assigned to cover the area of Surakarta and the newsroom. The results showed a change in the pattern of coverage, number, and broadcast pattern or news packaging model and changes in editorial policy. The orientation of the news is no longer merely to “worship” exclusivity. It requires high creativity so that it does not lose information. The pattern of coverage previously had to go by interviews and direct observations to become a mediated pattern. It became considered taboo for journalists in the era before the pandemic. Photos and videos no longer have to match the news narrative but can be used as substitute objects as long as they have relevance. The format of voice-over news has been changed a lot in the form of live broadcasts, and mini talk shows to fill the program's broadcast duration, which was affected by the decrease in the number of news reports reported by journalists during the pandemic.